The Influence of Globalisation on the Shift in Local Language and Cultural Identity - Lalombo, Agneta Sartika (Journal Corner of Education, Linguistics, and Literature, 2024)
Globalisation has led to significant changes in the use of regional languages and local cultural identities, particularly in Indonesia, a country renowned for its linguistic and cultural diversity. This study aimed to analyse the impact of globalisation on the decline in regional language use, identify the factors influencing the shift in local cultural identity, and explore adaptive strategies to preserve language and culture in the digital era. Employing a descriptive qualitative approach with a literature analysis method, this research examines various academic journals, books, and research reports published within the past decade. The findings indicate that globalisation has significantly contributed to the decline in the number of regional language speakers, with Indonesian and foreign languages increasingly dominating daily communication. Furthermore, global culture, disseminated through social media and the entertainment industry, has shifted young people’s interest away from local traditions. However, this study also highlights the potential of social media as a tool for revitalising local languages and cultures, with various digital initiatives successfully raising public awareness of cultural preservation. Strategies to sustain local language and culture include integrating regional languages into education, utilising digital technology, implementing government policies, promoting cultural awareness campaigns, and fostering collaboration with the creative industries. Nevertheless, this study has limitations, as it does not incorporate direct field data. Therefore, future research is recommended to adopt ethnographic approaches and quantitative analysis to measure the long-term effectiveness of digital strategies. The findings of this study are expected to serve as a reference for policymakers, educators, and cultural communities in formulating strategies to safeguard local languages and cultural heritage amidst the pressures of globalisation.